Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Effect of multipin atmospheric cold plasma treatment on color, capsaicin and microbial content of geographical indication-tagged Byadagi chili powder - Neha Tanwar; Sandeep N. Mudliar; Roopavathi C; Prasanna Vasu; Sukumar Debnath (Journal of Food Engineering, 2025)

Greening the oil industry: Microalgae biorefinery for sustainable oil-produced water treatment and resource recovery - Mohammad Sibtain Kadri; Nayana K.; Reda Fassi Fihri; Gholamreza Abdi; Sukumar C.; Arunkumar Kulanthaiyesu (Journal of Water Process Engineering, 2024)

Chromosome substitution lines with improved essential mineral nutrients and fiber quality traits in Upland cotton - Sukumar Saha; Haile Tewolde; Johnie N. Jenkins; Jack C. McCarty; David M. Stelly (Genetic Resources and Crop Evolution, 2023)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effect of chromosome substitutions from Gossypium barbadense L., G. tomentosum Nutt. Ex Seem and G. mustelinum Watt into G. hirsutum L. on cottonseed protein and oil content - Sukumar Saha; Nacer Bellaloui; Johnie N. Jenkins; Jack C. McCarty; David M. Stelly (Euphytica, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Genotypic comparisons of chromosomes 01, 04, and 18 from three tetraploid species of Gossypium in topcrosses with five elite cultivars of G. hirsutum L. - Johnie N. Jenkins; Jack C. McCarty; B. Todd Campbell; R. W. Hayes; Jixiang Wu; Sukumar Saha; David Stelly (Euphytica, 2017)

Removal of Cr(VI) using co-immobilized activated carbon and Bacillus subtilis: fixed-bed column study - C. Sukumar; V. Janaki; K. Vijayaraghavan; S. Kamala-Kannan; K. Shanthi (Clean Technologies and Environmental Policy, 2017)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Biosorption of chromium(VI) using Bacillus subtilis SS-1 isolated from soil samples of electroplating industry - C. Sukumar; V. Janaki; Seralathan Kamala-Kannan; K. Shanthi (Clean Technologies and Environmental Policy, 2014)

Mycotoxins produced by Fusarium spp. associated with Fusarium head blight of wheat in Western Australia - Diana C. Tan; Gavin R. Flematti; Emilio L. Ghisalberti; Krishnapillai Sivasithamparam; Sukumar Chakraborty; Friday Obanor; Kithsiri Jayasena; Martin J. Barbetti (Mycotoxin Research, 2012)

Removal of chromium using Rhizobium leguminosarum - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2012)

Mycotoxins produced by Fusarium species associated with annual legume pastures and ‘sheep feed refusal disorders’ in Western Australia - Diana C. Tan; Gavin R. Flematti; Emilio L. Ghisalberti; Krishnapillai Sivasithamparam; Sukumar Chakraborty; Friday Obanor; Martin John Barbetti (Mycotoxin Research, 2011)

Genetic effects of individual chromosomes in cotton cultivars detected by using chromosome substitution lines as genetic probes - Jixiang Wu; Johnie N. Jenkins; Jack C. McCarty; Sukumar Saha (Genetica, 2010)

Optimisation of extracellular tannase production from Paecilomyces variotii - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2010)

Genetic dissection of chromosome substitution lines of cotton to discover novel Gossypium barbadense L. alleles for improvement of agronomic traits - Sukumar Saha; Jixiang Wu; Johnie N. Jenkins; Jack C. McCarty; Russell Hayes; David M. Stelly (Theoretical and Applied Genetics, 2010)

Genetic changes in plant growth and their associations with chromosomes from Gossypium barbadense L. in G. hirsutum L - Jixiang Wu; Jack C. McCarty; Sukumar Saha; Johnie N. Jenkins; Russell Hayes (Genetica, 2009)

Genetic detection of node of first fruiting branch in crosses of a cultivar with two exotic accessions of upland cotton - Yufang Guo; Jack C. McCarty; Johnie N. Jenkins; Chuanfu An; Sukumar Saha (Euphytica, 2009)

Genetic association of lint yield with its components in cotton chromosome substitution lines - Jixiang Wu; Johnie N. Jenkins; Jack C. McCarty; Sukumar Saha; Richard Percy (Euphytica, 2008)

QTLs for node of first fruiting branch in a cross of an upland cotton, Gossypium hirsutum L., cultivar with primitive accession Texas 701 - Yufang Guo; Jack C. McCarty; Johnie N. Jenkins; Sukumar Saha (Euphytica, 2008)

An Objective Analysis of Support Vector Machine Based Classification for Remote Sensing - Thomas Oommen; Debasmita Misra; Navin K. C. Twarakavi; Anupma Prakash; Bhaskar Sahoo; Sukumar Bandopadhyay (Mathematical Geosciences, 2008)

Physiological and ultrastructural studies on glycerinated body wall of sea cucumber - Sukumar C NOSKOR; Kohzoh OHTSU; Akira MATSUNO (Fisheries Science, 2008)

Minimum population size, genetic diversity, and social structure of the Asian elephant in Cat Tien National Park and its adjoining areas, Vietnam, based on molecular genetic analyses - T. N. C. Vidya; Surendra Varma; Nguyen X. Dang; T. Van Thanh; R. Sukumar (Conservation Genetics, 2007)

Dioxin formation in pulp and paper mills of India - Neeta P. Thacker; Vaishali C. Nitnaware; Swapnesh K. Das; Sukumar Devotta (Environmental Science and Pollution Research, 2007)

Effects of chromosome 5sh from Gossypium barbadense L. on flower production in G. hirsutum L. - Jack C. McCarty; Jixiang Wu; Sukumar Saha; Johnie N. Jenkins; Russell Hayes (Euphytica, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Prediction of Arsenic in Bedrock Derived Stream Sediments at a Gold Mine Site Under Conditions of Sparse Data - Navin K. C. Twarakavi; Debasmita Misra; Sukumar Bandopadhyay (Natural Resources Research, 2006)

An additive-dominance model to determine chromosomal effects in chromosome substitution lines and other gemplasms - Jixiang Wu; Johnie. N. Jenkins; Jack C. McCarty; Sukumar Saha; David M. Stelly (Theoretical and Applied Genetics, 2006)

Social organization of the Asian elephant (Elephas maximus) in southern India inferred from microsatellite DNA - T. N. C. Vidya; R. Sukumar (Journal of Ethology, 2005)

Somatic embryo initiation and germination in diploid cotton (Gossypium arboreum L.) - Hamidou F. Sakhanokho; Allan Zipf; Kanniah Rajasekaran; Sukumar Saha; Govind C. Sharma; Peng W. Chee (In Vitro Cellular & Developmental Biology - Plant, 2004)

The effect of some ecological factors on the intestinal parasite loads of the Asian elephant (Elephas maximus) in southern India - T. N. C. Vidya; R. Sukumar (Journal of Biosciences, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)